2008
DOI: 10.3354/meps07605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen conditions on intracapsular development in two calyptraeid species with different modes of larval development

Abstract: Oxygen availability in the aggregation of offspring has been shown to be a critical factor affecting the survival and development of embryos in aquatic systems. It is not yet known, however, to what extent the capacity to provide O 2 to embryo aggregations may act on the time of parental protection (here encapsulation), ultimately determining indirect and direct embryonic development. We assessed O 2 conditions during encapsulation, the factors determining those conditions, and the consequences on embryo survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Protection against desiccation, osmotic changes, UV or predation are some of the numerous advantages of this strategy (for a review, see Przeslawski, 2004). In spite of the advantages of embryo packing in aquatic systems, encapsulated embryos must confront two important constraints during development: food and oxygen limitations (Pechenik, 1979;Strathmann and Stranthmann, 1995;Brante et al, 2008). The consequences of these constraints on species showing embryos with different feeding strategies are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Protection against desiccation, osmotic changes, UV or predation are some of the numerous advantages of this strategy (for a review, see Przeslawski, 2004). In spite of the advantages of embryo packing in aquatic systems, encapsulated embryos must confront two important constraints during development: food and oxygen limitations (Pechenik, 1979;Strathmann and Stranthmann, 1995;Brante et al, 2008). The consequences of these constraints on species showing embryos with different feeding strategies are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons with previous studies where isolated gastropod eggs or embryos were exposed to chronic hypoxia show a general concordance with the impacts on growth, development and survival that we observed in L. obtusata (but see discussion of velum plasticity below). Only around 1 in 10 eggs of the slipper limpet, Crepidula fornicata, survived a 3 day exposure to an environmental P O2 of 3.2 kPa (Brante et al, 2008) and no embryos of the nassarid Nassarius festivus hatched successfully when cultured in seawater of P O2 of just less than 1 kPa (Chan et al, 2008). It should be noted that both these P O2 values are considerably lower than we used in our study.…”
Section: Hypoxia-induced Developmental Plasticitymentioning
confidence: 40%
“…However, there is also evidence of negative effects even at P O2 values similar to those we used (8 kPa), which may not be classified by ecologists as being environmental hypoxia (Vaquer-Sunyer and Duarte, 2008). While the survival of the encapsulated slipper limpet, C. coquimbensis, was not significantly affected by exposure to P O2 of ∼11.5 kPa (Brante et al, 2008), Brante et al (2009) later found that aerobic metabolism of embryos of this species and the related C. fornicata decreased significantly at P O2 <12 kPa. Similarly, development, hatching and shell secretion of the encapsulated muricid snail Chorus giganteus were all compromised by culture in seawater of P O2 ∼10 kPa (Cancino et al, 2003(Cancino et al, , 2011 and embryonic development of N. festivus was significantly delayed when cultured at a P O2 of ∼7.6 kPa (Chan et al, 2008).…”
Section: Hypoxia-induced Developmental Plasticitymentioning
confidence: 75%
See 1 more Smart Citation
“…Indeed, encapsulation engenders some of the most extreme forms of parent-offspring conflict and sibling rivalry, including consumption of non-developing nurse eggs (oophagy) and of viable siblings (adelphophagy) [34]. Siblings not only compete for nutrients provided by their parents, but also for resources that are affected by the packaging per se, such as the availability of oxygen [35,36]. The ubiquity of egg masses, capsules and other forms of encapsulation in marine invertebrates suggests that competition among siblings occurs frequently.…”
Section: Marine Life Histories and The Opportunity For Kin Selectionmentioning
confidence: 99%